2016
DOI: 10.1021/acs.est.6b01685
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Concentrations of Halogenated Flame Retardants in the Atmospheric Fine Particles in Chinese Cities

Abstract: The concentrations of halogenated flame retardants (HFRs) in PM 2.5 were monitored for one year at 10 urban sites in China during 2013−2014. This study investigated four classes of HFRs: nine polybrominated diphenyl ethers (PBDEs), six nonbromodiphenyl ether (BDE) brominated flame retardants, two dechlorane plus (DP) flame retardants, and three chlorinated organophosphate flame retardants (OPFRs). Extremely high concentrations of BDE-209 and DBDPE were observed in only one city (Guangzhou), which was a consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 52 publications
8
40
4
Order By: Relevance
“…Only few studies investigated PM 2.5 -bound PBDEs in outdoor air (Table 3). Compared with PM 2.5 -bound ΣPBDEs in the previous studies (Dong et al, 2015;Liu et al, 2016), our values in Taiwanese outdoor air were comparable to outdoor air levels in the metropolis areas in China, but still 60 to 100-fold higher than the background levels of atmospheric PM 2.5 -bound PBDEs in East China Sea . Although outdoor PM 2.5 -bound Σ 12 PBDEs in the ambient air of Valencia, Spain were presented in extremely low magnitudes, the high molecular weights of PBDEs like octa-BDEs, nonaBDEs, and deca-BDEs were not analyzed in Beser's report (Beser et al, 2014).…”
Section: Resultssupporting
confidence: 74%
“…Only few studies investigated PM 2.5 -bound PBDEs in outdoor air (Table 3). Compared with PM 2.5 -bound ΣPBDEs in the previous studies (Dong et al, 2015;Liu et al, 2016), our values in Taiwanese outdoor air were comparable to outdoor air levels in the metropolis areas in China, but still 60 to 100-fold higher than the background levels of atmospheric PM 2.5 -bound PBDEs in East China Sea . Although outdoor PM 2.5 -bound Σ 12 PBDEs in the ambient air of Valencia, Spain were presented in extremely low magnitudes, the high molecular weights of PBDEs like octa-BDEs, nonaBDEs, and deca-BDEs were not analyzed in Beser's report (Beser et al, 2014).…”
Section: Resultssupporting
confidence: 74%
“…The P 10 OPE concentrations in PM 2.5 ranged from 0.54 ng m À3 to 20.0 ng m À3 (mean: 2.78 ± 3.00 ng m À3 ), which were lower than the concentrations in PM 2.5 in other developed areas of China, including Nanjing (7.25 ng m À3 ) and Chengdu (6.46 ng m À3 ) (Faiz et al, 2018;Yin et al, 2015). The mean concentration (1.82 ± 2.45 ng m À3 ) of three OPEs (TCEP, TCPP, and TDCPP) were much higher than those in a previous study in Xinxiang in 2014 (600 pg m À3 ) (Liu et al, 2016), suggesting worsening OPE pollution. Among the targeted OPEs, TCEP was the most abundant component in most samples (n ¼ 42), with a mean concentration of 1.07 ± 2.02 ng m À3 and range of 0.12e13.7 ng m À3 (Fig.…”
Section: Concentrations and Profilescontrasting
confidence: 62%
“…Therefore, PM 2.5 may carry or concentrate atmospheric OPEs during transport from urban areas to remote areas, or deposit them onto the surface of water and soil (Clark et al, 2017;Lai et al, 2015;Luo et al, 2016). The data related to OPEs in PM 2.5 are limited (Faiz et al, 2018;Liu et al, 2016;Yin et al, 2015), particularly data on the atmospheric transport of OPEs in PM 2.5 . Nonetheless, existing reports indicated that OPEs may undergo long-range migration (M€ oller et al, 2011;Salamova et al, 2014Salamova et al, , 2016, the OPEs pollution may be propagated via remote sources (Okonski et al, 2014), which requires more attention.…”
Section: Introductionmentioning
confidence: 99%
“…PM2.5 samples were collected from 10 urban cities in China (Beijing (BJ), Shanghai (SH), Guangzhou (GZ), Nanjing (NJ), Wuhan (WH), Taiyuan (TY), Chengdu (CD), Lanzhou (LZ), Guiyang (GY), and Xinxiang (XX)) during spring (SP), summer (S), autumn (A), and winter (W). Detailed descriptions of the sampling sites, sampling methods, and protocols are given in our previous paper 18 .…”
Section: Pm25 Sampling Organic Fraction Extraction and Wsf Extractionmentioning
confidence: 99%